Co-operative intermolecular kinetics of 2-oxoglutarate dependent dioxygenases may be essential for system-level regulation of plant cell physiology - Kundu, Siddhartha (Frontiers in Plant Science, 2015)
Chlorosis, a common manifestation of Fe-deficiency in plants occurs in soils with an alkaline pH and/or a high concentration of calcium carbonate (calcareous), and is an important cause of depressed yield. The core premise of this work is the notion that the response to waning ferrous iron in the cytosol of graminaceous root cells is a well orchestrated pathophysiological event, wherein the principal co-ordinator is not restricted to a single protein, but is an assortment of enzymes. The 2OG-dependent sequences comprise members present in all major kingdoms of life, and catalyze the release of carbon dioxide and succinic acid from 2-oxoglutarate, and the hydroxylation of a substrate molecule. This generic reaction is, in most cases accompanied by a specialized conversion of the product. Here, I present a model of iron deficiency sensing and response actuation in the root cells of graminaceous crops. This hypothesis is centered on the rationale that, iron is an essential co-factor for the catalytic process, and therefore, declining cytosolic levels of this micronutrient could trigger compensatory measures. Regression models of empirically available kinetic data for iron and alpha-ketoglutarate were formulated, analysed, and compared. The results, when viewed in the context of the superfamily responding as a unit to this abiotic stressor, suggest that the 2OG-sequences can indeed, work together to mitigate the effects of this noxious stimulus.